2017
DOI: 10.3389/fmed.2017.00178
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Frailty on the Risk of Conversion from Mild Cognitive Impairment to Alzheimer’s Disease: Evidences from a 5-Year Observational Study

Abstract: The frailty construct has increasingly been adopted in the field of cognitive disorders. The aim of the present study was to measure frailty in a cohort of individuals with mild cognitive impairment (MCI) and to explore whether frailty measures may consent to predict the risk of conversion to dementia. We retrospectively reviewed the clinical charts of outpatients with amnesic MCI (aMCI) consecutively recruited at our Department, and followed-up for 5 years. Individual frailty status was measured by means of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 27 publications
3
21
0
Order By: Relevance
“…It is not clear whether sex differences in mortality in mouse models of AD indicate sex-specific phenotypes, or differences in survival in response to the same degree of pathology. The sex differences in mortality in AD mouse models appears to correspond to what is seen in humans; men with AD generally have greater mortality risk than women (Sinforiani et al, 2010 ; Mielke et al, 2014 ; Mazure and Swendsen, 2016 ) and have a higher FI (Trebbastoni et al, 2017 ). In humans, the mechanism underlying this sex difference in lifespan is not well understood but may be related to sex differences in brain development and structure, in risk factors for AD (Mielke et al, 2014 ), or in the pathology of AD (Mielke et al, 2014 ; Mazure and Swendsen, 2016 ).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…It is not clear whether sex differences in mortality in mouse models of AD indicate sex-specific phenotypes, or differences in survival in response to the same degree of pathology. The sex differences in mortality in AD mouse models appears to correspond to what is seen in humans; men with AD generally have greater mortality risk than women (Sinforiani et al, 2010 ; Mielke et al, 2014 ; Mazure and Swendsen, 2016 ) and have a higher FI (Trebbastoni et al, 2017 ). In humans, the mechanism underlying this sex difference in lifespan is not well understood but may be related to sex differences in brain development and structure, in risk factors for AD (Mielke et al, 2014 ), or in the pathology of AD (Mielke et al, 2014 ; Mazure and Swendsen, 2016 ).…”
Section: Discussionmentioning
confidence: 88%
“…In terms of frailty, women have higher FI scores than men at all ages, but, paradoxically, have lower mortality risk (Mitnitski et al, 2002 ; Puts et al, 2005 ; Yang and Lee, 2010 ; Gordon et al, 2017 ). The FI is also related to cognitive decline in Alzheimer’s patients as increases in the FI are correlated with increased cognitive decline and a higher probability of converting from mild cognitive impairment (MCI) to AD (Kelaiditi et al, 2016 ; Trebbastoni et al, 2017 ). Increasing age, male sex and higher FI scores were associated with a higher probability of converting from MCI to AD in patients (Trebbastoni et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…A more rapid rate of increasing frailty is related to a more rapid loss of cognitive functions and low response to therapy [ 89 , 90 ]. Frailty level correlates with AD biomarkers [ 91 ] and the higher probability for mild cognitive impairment (MCI) to progress to AD [ 92 , 93 ]. We have recently suggested that frailty status could be a useful marker in preclinical assessment of novel AD therapeutics [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] Measuring each individual's degree of frailty may help identify those individuals without cognitive impairment most likely to develop MCI, 14 and those with MCI most likely to progress to dementia. 15 Critically, despite recent recommendations in support of preventing and mitigating frailty 16 -chiefly through lifestyle interventions that overlap with those proposed for dementia-it is not yet known whether frailty plays an equal role in dementia development in relation to a genetic predisposition to dementia. Recent evidence is mixed about whether a healthy lifestyle reduces dementia risk in those at high genetic risk.…”
Section: Introductionmentioning
confidence: 99%